Toner manufacturing method

The method of preparing a masterbatch and performing phase inversion emulsification with neutralization improves pigment dispersibility in toner production, addressing issues of coloring degree and fine line reproducibility, and enhancing image quality and fixing properties.

JP7608947B2Active Publication Date: 2025-01-07RICOH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021066328
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-09
Publication Date
2025-01-07
Estimated Expiration
2041-04-09

AI Technical Summary

Technical Problem

Existing toner production methods using phase inversion emulsification suffer from insufficient pigment dispersibility, leading to issues with coloring degree and fine line reproducibility.

Method used

A method involving the preparation of a masterbatch by kneading a colorant and resin, followed by dissolving it in an organic solvent to create an oil phase, mixing with an aqueous phase, and performing phase inversion emulsification to achieve an oil-in-water dispersion, with neutralization using an alkaline aqueous solution to improve dispersibility.

Benefits of technology

Enhances colorant dispersibility and fine line reproducibility in toner production, resulting in improved image quality and fixing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608947000001
    Figure 0007608947000001
  • Figure 0007608947000002
    Figure 0007608947000002
Patent Text Reader

Abstract

To provide a toner manufacturing method that can improve dispersibility of colorant in manufacture of toner using a phase inversion emulsification method and can manufacture toner having satisfactory pigmentation degree and thin line reproducibility.SOLUTION: A toner manufacturing method includes: a) a step of kneading colorant and resin to manufacture a masterbatch; b) a step of manufacturing an oil phase obtained by dissolving the masterbatch in an organic solvent; c) a step of mixing the organic solvent with water to manufacture an aqueous phase; and d) a step of adding the aqueous phase to the oil phase to perform phase inversion emulsification, thereby obtaining an oil-in-water type fluid dispersion.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a toner. [Background technology]

[0002] In recent years, there has been a demand for toners that have a lower environmental impact. To address this, for example, efforts are being made to reduce power consumption by improving the low-temperature fixing ability of the toner itself, and to reduce the amount of energy and chemicals used in the toner manufacturing process. Furthermore, there is an increasing demand for high image quality, including fine lines and color characteristics approaching those of offset printing.

[0003] As a method for improving the low-temperature fixing property of a toner, a method for lowering the glass transition temperature or softening point of a resin, a method for adding a crystalline resin, etc. are widely known. As a method for achieving high image quality, it is known to improve the reproduction of fine lines by using a toner with a small particle size and narrow particle size distribution, and to improve the color reproduction and coloring degree by improving the dispersion of a colorant. In addition, a pulverization method was used as a method for manufacturing a toner, but since it requires a lot of energy for manufacturing and there is a trend to reduce the diameter of a toner, chemical toners such as suspension polymerization have become mainstream. Summary of the Invention [Problem to be solved by the invention]

[0004] One method for reducing the amount of chemicals used in toner production is the phase inversion emulsification method, which can reduce the amount of surfactants. In the phase inversion emulsification method, the oil phase or the water phase is adjusted to stabilize the conditions during emulsion dispersion, thereby achieving a sharper particle size distribution of the resin particles (Patent Document 1). However, it has been found that this method is insufficient in dispersibility of the pigment in a toner containing a pigment as a colorant, resulting in problems in coloring degree and reproducibility of fine lines.

[0005] Therefore, an object of the present invention is to provide a method for producing a toner that can improve the dispersibility of a colorant in the production of a toner using a phase inversion emulsification method and that has good coloring degree and fine line reproducibility. [Means for solving the problem]

[0006] In order to solve the above problems, the method for producing a toner of the present invention comprises the steps of: a) mixing a colorant and a resin to prepare a master batch; b) preparing an oil phase by dissolving the master batch in an organic solvent; c) mixing an organic solvent and water to produce an aqueous phase; d) adding the aqueous phase to the oil phase to effect phase inversion emulsification, thereby obtaining an oil-in-water dispersion. fruit, In the step b, the master batch is dissolved in the organic solvent, and then neutralized with an alkaline aqueous solution. It is characterized by: Effect of the Invention

[0007] According to the present invention, it is possible to improve the dispersibility of a colorant in the production of a toner using a phase inversion emulsification method, and it is possible to provide a method for producing a toner with good coloring degree and fine line reproducibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The toner manufacturing method according to the present invention will be described below. Note that the present invention is not limited to the following embodiments, and may be modified, added, modified, deleted, or otherwise altered within the scope of what a person skilled in the art can conceive, and any embodiment is within the scope of the present invention as long as it exhibits the functions and effects of the present invention.

[0009] The method for producing the toner of the present invention comprises the steps of: a) mixing a colorant and a resin to prepare a master batch; b) preparing an oil phase by dissolving the master batch in an organic solvent; c) mixing an organic solvent and water to produce an aqueous phase; and d) adding the aqueous phase to the oil phase to effect phase inversion emulsification, thereby obtaining an oil-in-water dispersion.

[0010] (Process a: Masterbatch production process) In step a, a master batch is prepared by kneading a colorant and a resin. By preparing a master batch by kneading a colorant and a resin as in this step, it becomes possible to uniformly disperse the colorant and the resin.

[0011] <Resin> The resin used for preparing the master batch can be appropriately selected, but it is preferable that it is a resin that is soluble in an organic solvent and insoluble or almost insoluble in water. Examples of the resin used include polystyrene, styrene-acrylic copolymer, polyvinyl chloride, polyvinyl acetate, polymethacrylic acid ester, polymethyl acrylate, polyacrylic acid ester, polyacrylonitrile, epoxy resin, polyethylene, polyurethane, polyester, polyethylene terephthalate, polyamide, paraffin wax, etc. These may be used alone or in combination. From the viewpoint of obtaining good fixability, polyester resin is preferable.

[0012] <<Polyester resin>> When used as a toner for developing electrostatic latent images in electrophotography, good fixing properties can be obtained by using a resin having a polyester skeleton. Examples of the resin having a polyester skeleton include polyester resins and block polymers of polyester and resins having other skeletons. Among them, when using a polyester resin, it is preferable because the uniformity of the obtained colored resin particles is improved.

[0013] Examples of polyester resins include ring-opening polymerization products of lactones, condensation polymerization products of hydroxycarboxylic acids, and polycondensation products of polyol (1) and polycarboxylic acid (2). From the viewpoint of freedom in design, polycondensation products of polyol and polycarboxylic acid are preferred.

[0014] The weight average molecular weight of the polyester resin is usually 1000 to 30000, preferably 3000 to 15000, and more preferably 5000 to 12000. If it is less than 1000, the heat resistant storage stability may deteriorate, and if it exceeds 30000, good low-temperature fixability may not be obtained.

[0015] The glass transition temperature Tg of the polyester resin is preferably 35 to 80° C., more preferably 40 to 70° C., and even more preferably 45 to 65° C. If the temperature is less than 35° C., the resulting colored resin particles may deform when placed in a high-temperature environment such as midsummer, or the colored resin particles may stick together and may not be able to behave as particles. If the temperature exceeds 80° C., good fixability may not be obtained.

[0016] -Polyol- The polyol (1) may be a diol (1-1) or a trihydric or higher polyol (1-2), and is preferably (1-1) alone or a mixture of (1-1) and a small amount of (1-2).

[0017] Examples of the diol (1-1) include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxides of the above alicyclic diols (ethylene oxide, propylene oxide, butylene oxide, side, etc.) adducts; 4,4'-dihydroxybiphenyls such as 3,3'-difluoro-4,4'-dihydroxybiphenyl; bis(hydroxyphenyl)alkanes such as bis(3-fluoro-4-hydroxyphenyl)methane, 1-phenyl-1,1-bis(3-fluoro-4-hydroxyphenyl)ethane, 2,2-bis(3-fluoro-4-hydroxyphenyl)propane, 2,2-bis(3,5-difluoro-4-hydroxyphenyl)propane (also known as tetrafluorobisphenol A), and 2,2-bis(3-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane; bis(4-hydroxyphenyl)ethers such as bis(3-fluoro-4-hydroxyphenyl)ether; Examples of the bisphenols include alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts.

[0018] Among these, preferred are alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols, and particularly preferred are alkylene oxide adducts of bisphenols and their combined use with alkylene glycols having 2 to 12 carbon atoms.

[0019] Examples of the trihydric or higher polyol (1-2) include trihydric to octahydric or higher polyhydric aliphatic alcohols (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (trisphenol PA, phenol novolac, cresol novolac, etc.); and alkylene oxide adducts of the above trihydric or higher polyphenols.

[0020] -Polycarboxylic acid- The polycarboxylic acid (2) may be a dicarboxylic acid (2-1) or a tri- or higher carboxylic acid (2-2), and is preferably (2-1) alone or a mixture of (2-1) and a small amount of (2-2).

[0021] Examples of the dicarboxylic acid (2-1) include alkylene dicarboxylic acids (succinic acid, adipic acid, sebacic acid, etc.); alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.); aromatic dicarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.), 3-fluoroisophthalic acid, 2-fluoroisophthalic acid, 2-fluoroterephthalic acid, 2,4,5,6-tetrafluoroisophthalic acid, 2,3,5,6-tetrafluoroterephthalic acid, 5-trifluoro Examples of such dicarboxylic acids include methylisophthalic acid, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 2,2-bis(3-carboxyphenyl)hexafluoropropane, 2,2'-bis(trifluoromethyl)-4,4'-biphenyldicarboxylic acid, 3,3'-bis(trifluoromethyl)-4,4'-biphenyldicarboxylic acid, 2,2'-bis(trifluoromethyl)-3,3'-biphenyldicarboxylic acid, and hexafluoroisopropylidenediphthalic anhydride. Among these, preferred are alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms.

[0022] Examples of the trivalent or higher polycarboxylic acid (2-2) include aromatic polycarboxylic acids having 9 to 20 carbon atoms (eg, trimellitic acid, pyromellitic acid, etc.).

[0023] As the polycarboxylic acid (2), the acid anhydrides or lower alkyl esters (methyl esters, ethyl esters, isopropyl esters, etc.) of the above-mentioned compounds may be reacted with the polyol (1).

[0024] The ratio of polyol to polycarboxylic acid, expressed as the equivalent ratio [OH] / [COOH] of the hydroxyl group [OH] to the carboxyl group [COOH], is usually 2 / 1 to 1 / 2, preferably 1.5 / 1 to 1 / 1.5, and more preferably 1.3 / 1 to 1 / 1.3.

[0025] <Coloring agent> As the colorant used in the present invention, known dyes and pigments can be used, for example, carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, iridium yellow, iodine ... Soindolinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Kanmin BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pogment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, lithopone and mixtures thereof can be used.

[0026] <Mixing> The master batch can be prepared by kneading the above-mentioned colorant and the above-mentioned resin. For example, a general kneader such as a twin-screw extrusion kneader, a three-roll mill, or a lab blast mill can be used for the kneading process. An internal additive may be added during the kneading process. It is preferable to heat the kneading process, and the heating conditions can be appropriately set.

[0027] The ratio of the resin to the colorant in preparing the master batch can be appropriately selected, but is preferably, for example, 70:30 to 30:70 on a mass basis.

[0028] (Step b: Oil phase preparation step) In step b, the master batch is dissolved in an organic solvent to prepare an oil phase. By going through the step of preparing an oil phase by dissolving the master batch in an organic solvent, it is possible to prepare an oil phase in which the colorant and resin are uniformly dispersed.

[0029] In the preparation of the oil phase, a resin or the like may be used in addition to the organic solvent and the master batch. Furthermore, the term "dissolving" may be referred to as "dispersing", or may be referred to as "dissolving or dispersing". In this embodiment, the oil phase is prepared by dissolving the resin and the master batch in the organic solvent.

[0030] The oil phase may be prepared by gradually adding the resin, master batch, etc. to the organic solvent while stirring the organic solvent, and dissolving or dispersing the resin, master batch, etc. In the case of dispersion, a known dispersing machine, for example, a bead mill or a disk mill, may be used.

[0031] <Organic solvent> The organic solvent can be appropriately selected, and for example, a volatile organic solvent with a boiling point of less than 100° C. is preferred from the viewpoint of ease of removal in the case of removing the organic solvent in a later step. Examples of such organic solvents include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropyl alcohol, etc. These can be used alone or in combination of two or more kinds.

[0032] When the resin to be dissolved or dispersed in the organic solvent is a resin having a polyester skeleton, it is preferable to use an ester-based solvent such as methyl acetate, ethyl acetate, or butyl acetate, or a ketone-based solvent such as methyl ethyl ketone or methyl isobutyl ketone. In this case, the solubility can be increased. Among these, methyl acetate, ethyl acetate, and methyl ethyl ketone, which have high solvent removability, are more preferable. Among these, the use of ethyl acetate as the organic solvent is more preferable because it increases the selectivity of materials when preparing a master batch or an oil phase.

[0033] <Resin> The resin used in the oil phase preparation step can be appropriately selected, and for example, those listed in the master batch preparation step can be used. The resin used in the oil phase preparation step is preferably soluble in an organic solvent and insoluble or almost insoluble in water. Among them, polyester resin is preferable. The amount of resin added is preferably 200 to 600 mass% relative to the master batch.

[0034] <Prepolymer> In the oil phase preparation step, in addition to the above, a reactive precursor (also called a prepolymer) may be used. Reactive precursors include polyesters having groups capable of reacting with active hydrogen groups. Examples of the group capable of reacting with the active hydrogen group include an isocyanate group, an epoxy group, a carboxylic acid, an acid chloride group, etc. Among these, an isocyanate group is preferred because it is capable of introducing a urethane bond or a urea bond into the polyester resin. The reactive precursor may have a branched structure imparted by at least one of a trivalent or higher alcohol and a trivalent or higher carboxylic acid.

[0035] Examples of polyester resins containing isocyanate groups (also referred to as polyester resin (A)) include reaction products of polyester resins having active hydrogen groups and polyisocyanates. The polyester resins having active hydrogen groups are obtained, for example, by polycondensation of diols, dicarboxylic acids, and at least one of trivalent or higher alcohols and trivalent or higher carboxylic acids. The trivalent or higher alcohols and trivalent or higher carboxylic acids impart a branched structure to the polyester resins containing isocyanate groups.

[0036] Examples of the diol include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethyl ether. Examples of the alkylene oxide adducts include diols having an oxyalkylene group, such as ethylene glycol; alicyclic diols, such as 1,4-cyclohexanedimethanol and hydrogenated bisphenol A; alicyclic diols to which alkylene oxides, such as ethylene oxide, propylene oxide and butylene oxide, have been added; bisphenols, such as bisphenol A, bisphenol F and bisphenol S; and alkylene oxide adducts of bisphenols, such as bisphenols to which alkylene oxides, such as ethylene oxide, propylene oxide and butylene oxide, have been added.

[0037] Among these, from the viewpoint of controlling the glass transition temperature Tg of the polyester resin (A) to 20° C. or less, it is preferable to use an aliphatic diol having 3 to 10 carbon atoms, such as 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, or 3-methyl-1,5-pentanediol, and it is more preferable that these account for 50 mol % or more of the alcohol components in the resin. These diols may be used alone or in combination of two or more.

[0038] The polyester resin (A) is preferably an amorphous resin, and the melt viscosity during fixing is reduced by providing steric hindrance to the resin chain, which makes it easier to achieve low-temperature fixing. For this reason, the main chain of the aliphatic diol preferably has a structure represented by the following general formula (1).

[0039] [ka]

[0040] [In the formula, R1 and R2 each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an odd number from 3 to 9. However, in the n repeating units, R1 and R2 may be the same or different.]

[0041] Here, the main chain of the aliphatic diol in the present invention refers to a carbon chain that connects two hydroxyl groups of the aliphatic diol with the shortest number of carbon atoms. When the carbon number of the main chain is odd, the crystallinity decreases due to the odd-even nature, which is preferable. In addition, when the main chain has at least one alkyl group having 1 to 3 carbon atoms in the side chain, the interaction energy between the main chain molecules decreases due to the steric nature, which is more preferable.

[0042] Examples of the dicarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, dodecanedioic acid, maleic acid, and fumaric acid; and aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. In addition, anhydrides, lower (1 to 3 carbon atoms) alkyl esters, and halides of these may be used. Among these, from the viewpoint of controlling the Tg of the polyester resin (A) to 20° C. or less, aliphatic dicarboxylic acids having 4 to 12 carbon atoms are preferred, and it is more preferred to use them in an amount of 50% by mass or more of the carboxylic acid component in the resin. These dicarboxylic acids may be used alone or in combination of two or more.

[0043] Examples of the trihydric or higher alcohol include trihydric or higher aliphatic alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and sorbitol; trihydric or higher polyphenols such as trisphenol PA, phenol novolac, and cresol novolac; and alkylene oxide adducts of trihydric or higher polyphenols, such as those obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to trihydric or higher polyphenols.

[0044] Examples of the trivalent or higher carboxylic acid include trivalent or higher aromatic carboxylic acids, and particularly preferred are trivalent or higher aromatic carboxylic acids having 9 to 20 carbon atoms, such as trimellitic acid and pyromellitic acid. In addition, anhydrides, lower (carbon number 1 to 3) alkyl esters, and halides of these may also be used.

[0045] Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates.

[0046] The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. For example, 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-tolylene diisocyanate (TDI), crude TDI, 2,4'- and / or 4,4'-diphenylmethane diisocyanate (MDI), crude MDI [phosgenation product of crude diaminophenylmethane [condensation product of formaldehyde and aromatic amine (aniline) or mixture thereof; mixture of diaminodiphenylmethane and a small amount (e.g., 5 to 20% by mass) of trifunctional or higher polyamine], polyallyl polyisocyanate, aromatic diisocyanates such as 1,5-naphthylene diisocyanate, 4,4',4''-triphenylmethane triisocyanate, m- and p-isocyanatophenylsulfonyl isocyanate; ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), dodecamethylene diisocyanate, 1,6,11-undecane triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2 Aliphatic diisocyanates such as 2-isocyanatoethyl-2,6-diisocyanatohexanoate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate; isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), bis(2-isocyanatoethyl)-4-cyclohexyl Examples of the isocyanate include alicyclic diisocyanates such as xene-1,2-dicarboxylate, 2,5- and 2,6-norbornane diisocyanate; araliphatic diisocyanates such as m- and p-xylylene diisocyanate (XDI), α,α,α',α'-tetramethylxylylene diisocyanate (TMXDI); trivalent or higher polyisocyanates such as lysine triisocyanate, diisocyanate-modified products of trivalent or higher alcohols; and modified products of these isocyanates, and mixtures of two or more of these may also be used.Examples of the modified isocyanate include modified products containing a urethane group, a carbodiimide group, an allophanate group, a urea group, a biuret group, a uretdione group, a uretoimine group, an isocyanurate group, and an oxazolidone group.

[0047] <Charge control agent> In addition to the above, a charge control agent and the like may be added to the oil phase. As the charge control agent, known ones can be used, such as nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.

[0048] Specifically, for example, the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (all manufactured by Hodogaya Chemical Co., Ltd.), the quaternary ammonium salt Copy Charge PSY VP2038, the triphenylmethane derivative Copy Blue PR, the quaternary ammonium salt Copy Charge NEG VP2036, and Copy Charge NX. Examples of suitable pigments include VP434 (all manufactured by Hoechst), LRA-901, the boron complex LR-147 (manufactured by Nippon Carlit), copper phthalocyanine, perylene, quinacridone, azo pigments, and other polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts.

[0049] The charge control agent may be used in an amount that allows the agent to exhibit its performance and does not impair fixability, etc. When contained in the toner, the amount is preferably 0.5 to 5 mass % and more preferably 0.8 to 3 mass % in the toner.

[0050] <Neutralization> In the oil phase preparation step, the master batch is dissolved in an organic solvent to obtain an oil phase, and the oil phase may then be neutralized with an alkaline aqueous solution. Examples of the alkaline aqueous solution include an aqueous ammonia solution and sodium hydroxide. Neutralizing the oil phase has the advantage of improving the water dispersibility of the resin and facilitating phase inversion emulsification.

[0051] (Step c: water phase preparation step) In step c, an organic solvent and water are mixed to prepare an aqueous phase. By going through the step of mixing an organic solvent and water to prepare an aqueous phase, it is possible to prevent the solvent from dissolving into water when the aqueous phase and the oil phase are dissolved, which would cause the conditions during emulsification to change, and sharp nano-sized particles can be prepared. Furthermore, the particle size distribution of the toner becomes sharp, improving the reproducibility of fine lines in images. It is not important to prepare the aqueous phase or the oil phase first.

[0052] The organic solvent used for preparing the aqueous phase can be appropriately selected, and for example, the organic solvents listed in the oil phase preparation step can be used. It is preferable that the organic solvent in step b (oil phase preparation step) is the same as the organic solvent in step c (aqueous phase preparation step). By using the same organic solvent, it is possible to minimize the variation caused by the solvent dissolving into water during emulsification.

[0053] Furthermore, it is more preferable that the organic solvent in the step b and the organic solvent in the step c are ethyl acetate. In this case, the advantage of using the same organic solvent in the steps b and c is obtained, and the use of ethyl acetate as the organic solvent increases the selectivity of materials when preparing a master batch or an oil phase, which is more preferable.

[0054] The mixing ratio of the organic solvent and water can be appropriately selected. It is preferable to prepare an aqueous solution in which the amount of the dissolved organic solvent is 80% or more of the saturated solubility amount by using the organic solvent and water. By making the amount of the organic solvent 80% or more of the saturated solubility amount, the amount of the organic solvent eluted from the oil phase to the aqueous phase can be reduced.

[0055] The aqueous phase may contain, in addition to the above, a surfactant, such as alkylbenzenesulfonate.

[0056] (Step d: Phase inversion emulsification step) In step d, the aqueous phase is added to the oil phase to effect phase inversion emulsification, thereby obtaining an oil-in-water dispersion. By passing through the step of adding the aqueous phase to the oil phase to effect phase inversion from the water-in-oil dispersion to the oil-in-water dispersion, granulation can be performed with a reduced amount of surfactant used, and nano-sized resin particles in which the colorant is uniformly dispersed can be produced.

[0057] In addition, a microparticle dispersion can be obtained by the phase inversion emulsification in this embodiment, and particles in which the colorant is uniformly dispersed can be obtained. Furthermore, by producing a toner by aggregating such particles, the toner has reduced bias of the colorant, and a high-quality image with good color characteristics can be obtained.

[0058] <Solvent removal process> In the step d (phase inversion emulsification step) in this embodiment, a solvent removal step may be carried out. The solvent removal step may be included in the emulsion phase inversion step, or may be separate from the emulsion phase inversion step.

[0059] To remove the organic solvent from an oil-in-water dispersion (also called a microparticle dispersion or a colored microparticle dispersion), for example, a method can be adopted in which the temperature is gradually raised while stirring the entire system, and the organic solvent in the droplets is evaporated and removed. In addition, a method can be used in which the obtained colored microparticle dispersion is sprayed into a dry atmosphere while stirring, and the organic solvent in the droplets is completely removed. In addition, a method can be used in which the pressure is reduced while stirring the colored microparticle dispersion, and the organic solvent is evaporated and removed. The latter two methods can be used in combination with the first method.

[0060] The drying atmosphere in which the colored fine particle dispersion is sprayed generally includes, for example, air, nitrogen, carbon dioxide, a gas obtained by heating combustion gas, etc., and in particular, various air streams heated to a temperature equal to or higher than the boiling point of the highest boiling point solvent used. In such a method, the desired quality can be obtained sufficiently by short-term treatment with a spray dryer, a belt dryer, a rotary kiln, etc.

[0061] (Step e: agglomeration step) In this embodiment, step e (aggregation step) may be performed. In step e, the oil-in-water dispersion is aggregated after step d. For example, the oil-in-water dispersion is aggregated while being stirred, so that the particle size can be adjusted to any desired size. In the aggregation step, a method of adding an aggregating agent, a method of adjusting pH, etc. may be used. When the aggregating agent is added, it may be added as it is, but it is preferable to make an aqueous solution of the aggregating agent, since this can prevent localized high concentration. In addition, it is preferable to gradually add the aggregating salt while watching the particle size of the colored particles.

[0062] The temperature of the dispersion during aggregation is preferably near the glass transition temperature Tg of the resin used. If the liquid temperature is too low, aggregation does not proceed well, which may result in poor efficiency, whereas if the liquid temperature is too high, the aggregation rate increases, which may result in the generation of coarse particles and a poor particle size distribution.

[0063] In the aggregation process, aggregation is stopped when the target particle size is reached. Methods for stopping aggregation include adding a salt or a chelating agent with a low ionic valence, adjusting the pH, lowering the temperature of the dispersion, and adding a large amount of an aqueous medium to dilute the concentration. By the above methods, a dispersion of colored aggregated particles can be obtained. The dispersion obtained by the aggregation process may be called an aggregated particle dispersion, a colored aggregated particle dispersion, or the like. The particles in these dispersions may be called aggregated particles, or the like.

[0064] In the aggregation step, wax may be added as a release agent, or a crystalline resin may be added for low-temperature fixability. In that case, it is preferable to prepare a dispersion liquid in which wax is dispersed in an aqueous medium, or a dispersion liquid of a crystalline resin in the same manner, and mix it with the colored particle dispersion liquid before aggregation. In this case, aggregated particles in which the wax or crystalline resin is uniformly dispersed can be obtained.

[0065] <Flocculant> As the flocculant, a known one can be used. For example, metal salts of monovalent metals such as sodium and potassium, metal salts of divalent metals such as calcium and magnesium, and metal salts of trivalent metals such as iron and aluminum can be used. Although not particularly limited, the flocculant is preferably added in an amount of, for example, 1 to 10 mass% relative to the solid content of the oil phase.

[0066] <Release agent> Wax can be used as a release agent. The wax is not particularly limited and can be appropriately selected depending on the purpose, but a release agent with a low melting point of 50°C to 120°C is preferable. The release agent with a low melting point is dispersed in the resin, and effectively acts as a release agent between the fixing roller and the toner interface, thereby improving hot offset properties even in an oil-less case (no release agent such as oil is applied to the fixing roller).

[0067] Suitable examples of the release agent include waxes. Examples of the waxes include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, wood wax, and rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusine; and petroleum waxes such as paraffin, microcrystalline, and petrolatum. In addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax and polyethylene wax; synthetic waxes such as esters, ketones, and ethers; and the like. Furthermore, fatty acid amides such as 12-hydroxystearic acid amide, stearic acid amide, phthalic anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups on the side chains may be used. These may be used alone or in combination of two or more.

[0068] The melting point of the wax is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50° C. to 120° C., and more preferably 60° C. to 90° C. If the melting point is 50° C. or higher, the wax can be prevented from adversely affecting the heat resistance storage stability, and if the melting point is 120° C. or lower, the problem of cold offset occurring during fixing at low temperatures can be effectively prevented.

[0069] The melt viscosity of the wax is preferably 5 cps to 1,000 cps, more preferably 10 cps to 100 cps, as measured at a temperature 20° C. higher than the melting point of the wax. If the melt viscosity is 5 cps or more, the release property can be prevented from decreasing, and if it is 1,000 cps or less, the effects of hot offset resistance and low-temperature fixability can be sufficiently exhibited.

[0070] The wax content in the toner is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0% by mass to 40% by mass, and more preferably 3% by mass to 30% by mass. If the wax content is 40% by mass or less, the fluidity of the toner can be prevented from deteriorating.

[0071] <Crystalline polyester resin> In addition to the above, a crystalline polyester resin may be used. The crystalline polyester resin is obtained from a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic acid anhydride, or a polycarboxylic acid ester.

[0072] In the present invention, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, as described above. Modified polyester resins, such as prepolymers and resins obtained by subjecting the prepolymers to a crosslinking and / or elongation reaction, do not belong to the crystalline polyester resin.

[0073] <<Polyhydric alcohol>> The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.

[0074] Examples of the diol include saturated aliphatic diols. Examples of the saturated aliphatic diol include linear saturated aliphatic diols and branched saturated aliphatic diols. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. In addition, if the carbon number of the saturated aliphatic diol exceeds 12, it becomes difficult to obtain a practical material.

[0075] Examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanedecanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of the high crystallinity of the crystalline polyester resin and excellent sharp melt properties.

[0076] Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0077] <<Polycarboxylic acids>> The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include divalent carboxylic acids and trivalent or higher carboxylic acids.

[0078] Examples of the divalent carboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid; and the like. Further examples include anhydrides of these acids and lower (carbon number 1 to 3) alkyl esters of these acids.

[0079] Examples of the trivalent or higher carboxylic acid include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower (carbon number 1 to 3) alkyl esters thereof. These may be used alone or in combination of two or more.

[0080] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms, which provides high crystallinity and excellent sharp melting properties, thereby enabling the toner to exhibit excellent low-temperature fixing properties.

[0081] In addition, as a method for controlling the crystallinity and softening point of a crystalline polyester resin, there can be mentioned a method of designing and using a non-linear polyester obtained by adding a trivalent or higher polyhydric alcohol such as glycerin to the alcohol component during polyester synthesis, or a trivalent or higher polycarboxylic acid such as trimellitic anhydride to the acid component and carrying out condensation polymerization.

[0082] The molecular structure of the crystalline polyester resin in this embodiment can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 to the δ of olefin CH One example is one that has absorption based on (out-of-plane bending vibration).

[0083] Regarding the molecular weight, from the viewpoint that a low molecular weight with a sharp molecular weight distribution is excellent in low temperature fixability, and a large amount of low molecular weight components deteriorates heat resistance storage stability, the following has been found to be preferable, for example. In the molecular weight distribution by GPC of the soluble portion in o-dichlorobenzene, the molecular weight distribution diagram with the horizontal axis being log(M) and the vertical axis being weight % has a peak position in the range of 3.5 to 4.0, the half width of the peak is 1.5 or less, and the weight average molecular weight (Mw) is preferably 3,000 to 30,000, the number average molecular weight (Mn) is 1,000 to 10,000, and Mw / Mn is 1 to 10. Furthermore, the weight average molecular weight (Mw) is preferably 5,000 to 15,000, the number average molecular weight (Mn) is preferably 2,000 to 10,000, and Mw / Mn is preferably 1 to 5.

[0084] From the viewpoint of the affinity between paper and resin, the acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more in order to achieve the desired low-temperature fixability. In addition, for the preparation of fine particles by phase inversion emulsification, the acid value is more preferably 7 mgKOH / g or more. On the other hand, in order to improve hot offset properties, the acid value is preferably 45 mgKOH / g or less. In addition, the hydroxyl value of the crystalline polymer is preferably 0 to 50 mgKOH / g, more preferably 5 to 50 mgKOH / g, in order to achieve a predetermined low-temperature fixability and good charging properties.

[0085] (Process f: Fusion process) In this embodiment, a step f (fusion step) may be performed. In the fusion step, the aggregated particles obtained in the aggregation step are fused by heat treatment, so that unevenness can be reduced. Fusion can be performed by heating a dispersion of colored aggregated particles while stirring. The temperature of the liquid is preferably near a temperature exceeding the glass transition temperature Tg of the resin used.

[0086] (Step g: washing or drying step) In this embodiment, step g (cleaning and drying steps) may be performed. Since the toner particle dispersion obtained by the above method may contain sub-materials such as coagulating salts in addition to the toner particles, it is preferable to perform cleaning in order to extract only the toner particles from the dispersion.

[0087] The washing method of the toner particles includes, for example, a centrifugation method, a vacuum filtration method, a filter press method, and the like, but is not particularly limited in the present invention. Any of the methods can obtain a cake of toner particles, but if the toner particles cannot be washed sufficiently in one operation, the obtained cake may be dispersed again in an aqueous solvent to form a slurry, and the process of extracting the toner particles by any of the above methods may be repeated. In addition, if washing is performed by the vacuum filtration method or the filter press method, a method may be adopted in which the aqueous solvent is penetrated into the cake to wash away the secondary material embraced by the colored resin particles. The aqueous solvent used for this washing can be water or a mixed solvent obtained by mixing water with an alcohol such as methanol or ethanol. Considering the cost and the environmental load due to wastewater treatment, it is preferable to use water.

[0088] Since the washed toner particles contain a large amount of the aqueous medium, the toner particles can be obtained by drying and removing the aqueous medium. For the drying method, a dryer such as a spray dryer, a vacuum freeze dryer, a reduced pressure dryer, a stationary shelf dryer, a movable shelf dryer, a fluidized bed dryer, a rotary dryer, or an agitator dryer can be used.

[0089] The dried toner particles are preferably dried until the moisture content is finally reduced to less than 1%. In addition, the colored resin particles after drying may be in the form of soft aggregates, and if this causes inconvenience during use, the particles may be disintegrated using a device such as a jet mill, a Henschel mixer, a super mixer, a coffee mill, an Oster blender, or a food processor to break up the soft aggregates.

[0090] (Step h: Annealing step) In this embodiment, step h (annealing step) may be performed. When a crystalline resin is added, the non-crystalline resin and the crystalline resin are phase-separated by performing an annealing treatment after drying, and the fixing property is improved. Specifically, the toner may be stored for 10 hours or more at a temperature near the glass transition temperature Tg of the resin.

[0091] (Process i: External addition process) In this embodiment, step i (external addition step) may be performed. Inorganic fine particles, polymer fine particles, cleaning aids, etc. may be added and mixed into the toner particles obtained in this embodiment in order to provide them with fluidity, chargeability, cleaning properties, etc. Specific mixing means include a method of applying an impact force to the mixture using a blade rotating at high speed, and a method of introducing the mixture into a high-speed air stream, accelerating the mixture, and causing the particles to collide with each other or the composite particles with an appropriate collision plate.

[0092] Examples of equipment include an Angmill (manufactured by Hosokawa Micron Corporation), a modified I-type mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, a hybridization system (manufactured by Nara Machinery Works, Ltd.), a Cryptron system (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar.

[0093] <External additives> The primary particle diameter of the inorganic fine particles is preferably 5 nm to 2 μm, and more preferably 5 nm to 500 nm. The specific surface area as measured by the BET method is preferably 20 to 500 m. 2 The content of the inorganic fine particles is preferably 0.01 to 5% by mass of the toner.

[0094] Specific examples of inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, pengallo, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride.

[0095] Examples of polymeric fine particles include polystyrene obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization, methacrylic acid ester or acrylic acid ester copolymers, polycondensation systems such as silicone, benzoguanamine, and nylon, and polymer particles made of thermosetting resins.

[0096] Such external additives can be surface-treated to increase hydrophobicity and prevent deterioration of flow properties and charging properties even under high humidity. For example, silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, modified silicone oils, etc. are preferred surface treatment agents.

[0097] In addition to the above, a cleaning property improver may be used as an external additive. Examples of cleaning property improvers for removing the developer remaining on the photoconductor or primary transfer medium after transfer include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, and polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles. The polymer fine particles preferably have a relatively narrow particle size distribution and a volume average particle size of 0.01 μm to 1 μm.

[0098] (measurement) <Particle size measurement of dispersion liquid> The particle size of the resin dispersion in the present invention can be measured, for example, using a Nanotrack particle size distribution analyzer UPA-EX150 (Nikkiso Co., Ltd., dynamic light scattering method / laser Doppler method). As a specific measurement method, the dispersion in which the resin fine particles are dispersed is adjusted to a measurement concentration range and measured. At that time, a background measurement is performed in advance using only the dispersion solvent of the dispersion. With this measurement method, it is possible to measure the volume average particle size range of the resin fine particles used in the present invention, from several tens of nm to several μm. In the present invention, the particle size refers to the volume average particle size (volume average diameter).

[0099] <Measuring method of melting point and glass transition temperature (Tg)> The glass transition temperature Tg in the present invention can be measured, for example, by using a DSC system (differential scanning calorimeter) ("Q-200", manufactured by TA Instruments). Specifically, the melting point and glass transition temperature of a sample can be measured by the following procedure. First, about 5.0 mg of the target sample is placed in an aluminum sample container, the sample container is placed on a holder unit, and set in an electric furnace. Next, in a nitrogen atmosphere, the sample is heated from -80°C to 150°C at a heating rate of 10°C / min (first heating). After that, the sample is cooled from 150°C to -80°C at a heating rate of 10°C / min, and further heated to 150°C at a heating rate of 10°C / min (second heating). During each of the first and second heating, a DSC curve is measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments). From the obtained DSC curves, the DSC curve at the first temperature rise can be selected using the analysis program in the Q-200 system, and the glass transition temperature at the first temperature rise of the target sample can be obtained. Similarly, the DSC curve at the second temperature rise can be selected, and the glass transition temperature at the second temperature rise of the target sample can be obtained. In the present invention, Tg refers to the glass transition temperature at the second heating step.

[0100] <Molecular weight> The molecular weight of the polyester resin, vinyl copolymer resin, etc. used is measured by GPC (gel permeation chromatography) under the following conditions, unless otherwise specified. Equipment: HLC-8220GPC (Tosoh Corporation) Column: TSKgel SuperHZM-Mx3 ·Temperature: 40℃ Solvent: THF (tetrahydrofuran) ·Flow rate: 0.35mL / min Sample: 0.01mL of sample with a concentration of 0.05 to 0.6% From the molecular weight distribution of the toner resin measured under the above conditions, the weight average molecular weight Mw is calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample. The monodisperse polystyrene standard sample is 5.8×10 2 , 1.085×10 4 , 5.95×10 4 , 3.2×10 5 , 2.56×10 6 , 2.93×10 3 , 2.85×10 4 , 1.48×10 5 , 8.417×10 5 , 7.5×10 6 Ten items from the above were used. EXAMPLES

[0101] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0102] (Preparation of polyester resin 1) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 2 mol ethylene oxide adduct of bisphenol A / 3 mol propylene oxide adduct of bisphenol A (molar ratio 40 / 60) as a diol component, terephthalic acid / adipic acid (molar ratio 85 / 15) as a dicarboxylic acid component, and 3.5 mol% trimethylolpropane based on the total monomer amount were added so that the molar ratio of hydroxyl group to carboxylic acid (OH / COOH) was 1.2. Furthermore, 1,000 ppm of tetrabutyl orthotitanate based on the total monomer amount was added as a condensation catalyst, and the temperature was raised to 230°C over 2 hours under a nitrogen stream, and the reaction was carried out for 5 hours while distilling off the generated water. Then, the mixture was reacted for 4 hours under reduced pressure of 5mmHg to 15mmHg, and cooled to 180°C. Then, 1.0 mol% of trimellitic anhydride based on the total monomer amount and 200 ppm of tetrabutyl orthotitanate based on the total monomer amount were added, and the mixture was reacted at normal pressure and 180°C for 1 hour. Then, the mixture was further reacted for 3 hours under reduced pressure of 5mmHg to 20mmHg. In this way, a [polyester resin 1] was obtained, which has a glass transition temperature Tg of 57°C and a weight average molecular weight of 7,700, as determined from the DSC curve of the first heating cycle by DSC (differential scanning calorimetry).

[0103] (Preparation of vinyl resin 1) 390 parts by mass of 0.1 mol / L Na3PO4 aqueous solution was added to 1150 parts by mass of pure water, and the mixture was stirred at 10,000 rpm using a mechanical disperser CLEARMIX (registered trademark) (manufactured by M-Technique Co., Ltd.) To this, 58 parts by mass of 1.0 mol / L CaCl2 aqueous solution was gradually added to prepare a dispersion containing Ca3(PO4)2. The following compounds were mixed and dissolved to prepare a polymerizable monomer composition, which was then added to the dispersion stirred at 8000 rpm with CLEARMIX, and further stirred for 30 minutes to prepare a polymerizable monomer composition dispersion in which droplets of the polymerizable monomer composition were dispersed.

[0104] Styrene 80 parts by weight n-Butyl acrylate 20 parts by weight 2,2-Azobis(2,4-dimethylvaleronitrile) 2.7 parts by mass

[0105] This polymerizable monomer composition dispersion was put into a reaction vessel equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and polymerization treatment was carried out for 5 hours at a temperature of 60°C in the reaction vessel while stirring under a nitrogen stream. Furthermore, the temperature in the reaction vessel was raised to 80°C and polymerization treatment was carried out for 10 hours, and then the reaction vessel was cooled to room temperature. As a result, a binder resin was produced, and hydrochloric acid was added to the produced binder resin to dissolve Ca3(PO4)2, followed by washing with water, filtration, and drying to produce amorphous [vinyl resin 1]. The weight average molecular weight Mw of [vinyl resin 1] was 35,000, and the glass transition temperature Tg was 55°C.

[0106] (Masterbatch Production) [Polyester resin 1] and Pigment Red 269 were premixed in a ratio of 1:1 using a Henschel mixer (Mitsui Miike Chemical Engineering Co., Ltd., FM20B), and then melted and kneaded at a temperature of 130°C using a twin-screw kneader (Ikegai Co., Ltd., PCM-30). The resulting kneaded product was rolled to a thickness of 2.7 mm using a roller, cooled to room temperature using a belt cooler, and coarsely pulverized to 200 μm to 300 μm using a hammer mill. In this way, [Master batch] was obtained.

[0107] (Preparation of Crystalline Polyester Resin Dispersion C-1) In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 1,6-hexanediol and sebacic acid were charged so that the ratio of OH groups to COOH groups (OH / COOH) was 1.1. The mixture was reacted while discharging water together with 500 ppm titanium tetraisopropoxide relative to the mass of the charged raw materials, and finally heated to 235°C and reacted for 1 hour. Then, the mixture was reacted for 6 hours under reduced pressure of 10 mmHg or less. Then, the temperature was set to 185°C, trimellitic anhydride was added so that the molar ratio with COOH groups was 0.053, and the mixture was reacted for 2 hours with stirring to obtain [Crystalline polyester resin C-1]. Into a four-neck flask, 55 parts by weight of [Crystalline polyester resin C-1], 40 parts by weight of methyl ethyl ketone, and 5 parts by weight of 2-propyl alcohol were added. Then, the mixture was heated at the melting point temperature of [Crystalline polyester resin C-1] while stirring to dissolve [Crystalline polyester resin C-1]. Then, 28% by weight of ammonia aqueous solution was added so that the neutralization rate was 400%. The neutralization rate was calculated from the acid value of [Crystalline polyester resin C-1]. Furthermore, 130 parts by weight of ion-exchanged water was gradually added to carry out phase inversion emulsification, and then the solvent was removed. Then, ion-exchanged water was added to adjust the solid content concentration (concentration of crystalline polyester resin) to 25% by mass, and [Crystalline polyester resin dispersion C-1], which is a binder resin dispersion for toner, was obtained. The particle size of the crystalline polyester resin in [Crystalline polyester resin dispersion C-1] was 200 nm.

[0108] (Production of wax emulsion 1) To 100 parts by weight of ion-exchanged water, 28 parts by weight of HNP-9 (manufactured by Nippon Seiro) as a wax and Sanisol B50 as a surfactant were added. This was dispersed in a homogenizer while being heated to 90°C, to obtain [Wax Emulsion 1]. The solid content was 30%.

[0109] Example 1 <Oil phase preparation process, aqueous phase preparation process, and phase inversion emulsification process> In a four-neck flask, 90 parts by weight of [polyester resin 1], 20 parts by weight of [master batch], and 120 parts by weight of ethyl acetate were added and stirred to dissolve or disperse the mixture. Then, 5 parts by weight of a 28% by mass aqueous ammonia solution was added while stirring to obtain a neutralization rate of 500%, thereby preparing an oil phase. In addition, an aqueous solution was prepared by adding ethyl acetate to 300 parts by weight of ion-exchanged water so that the amount was 100% based on the saturated solubility amount, and a surfactant ABS (alkylbenzene sulfonate) was further added so that the amount was 1% based on the total amount of the ion-exchanged water and ethyl acetate, to prepare an aqueous phase. The water phase was gradually added to the oil phase to effect phase inversion emulsification, and the solvent was then removed to obtain [Slurry 1]. The particle size of [Slurry 1] was measured to be 0.50 μm. The solid content was adjusted to 20%.

[0110] <Aggregation process and fusion process> 100 parts by weight of [Slurry 1], 5.0 parts by weight of [Crystalline polyester resin dispersion C-1], 5.0 parts by weight of [Wax emulsion 1], and 300 parts by weight of ion-exchanged water were placed in a container and stirred for 1 minute. Next, 20 parts by weight of 5% magnesium chloride solution was dropped based on the solid content, and the mixture was stirred for another 5 minutes, and then heated to 60°C. After that, when the particle size reached 5.0 μm, 40 parts by weight of sodium chloride was added to terminate the aggregation process, and [Aggregated slurry 1] was obtained. [Aggregated slurry 1] was heated to 70°C while stirring, and cooled when the desired circularity of 0.96 was reached, and [Toner dispersion 1] was obtained.

[0111] <Annealing step and cleaning or drying step> [Toner dispersion liquid 1] was stored at 45° C. for 10 hours, filtered under reduced pressure, and washed and dried as follows. (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 900 parts of ion-exchanged water was added to the filter cake of (1), and ultrasonic vibration was applied and mixed with a TK homomixer (rotation speed 12,000 rpm for 30 minutes), and then the mixture was filtered under reduced pressure. This operation was repeated until the electrical conductivity of the reslurry liquid became 10 μC / cm or less, and then the mixture was filtered to obtain [Filter cake 1]. The [filter cake 1] was dried in a circulating air dryer at 45° C. for 72 hours and sieved through a 75 μm mesh to obtain [colored resin particles 1].

[0112] <External attachment> To 100 parts by weight of [Colored Resin Particles 1], 2.5 parts by weight of inorganic fine particles TS530 manufactured by Cabosil Corporation was added, and mixed for 10 minutes at 40 m / s in a Henschel mixer to obtain the toner of Example 1.

[0113] Example 2 A toner of Example 2 was obtained in the same manner as in Example 1, except that in the oil phase preparation step, [polyester resin 1] was replaced with [vinyl resin 1].

[0114] Example 3 A toner of Example 3 was obtained in the same manner as in Example 1, except that in the aqueous phase preparation step of Example 1, ethyl acetate was replaced with MEK (methyl ethyl ketone).

[0115] (Examples 4 and 5) The toners of Examples 4 and 5 were obtained in the same manner as in Example 1, except that in the aqueous phase preparation step of Example 1, the saturated dissolution amount was changed from 100% to 80% in Example 4 and 60% in Example 5.

[0116] Example 6 The toner of Example 6 was obtained in the same manner as in Example 1, except that in the oil phase preparation step and the aqueous phase preparation step, the ethyl acetate in the oil phase was changed to MEK, and the ethyl acetate in the aqueous phase was changed to MEK.

[0117] Comparative Example 1 A toner of Comparative Example 1 was obtained in the same manner as in Example 1, except that in the oil phase preparation step, 20 parts by weight of the [master batch] was replaced with 10 parts by weight of Pigment Red 269.

[0118] Comparative Example 2 A toner of Comparative Example 2 was obtained in the same manner as in Example 1, except that ethyl acetate was not used in the aqueous phase preparation step.

[0119] Comparative Example 3 A toner of Comparative Example 3 was obtained in the same manner as in Example 1, except that in the oil phase preparation step of Example 1, the master batch was not added, and in the aggregation step and fusion step, 10 parts by weight of Pigment Red 269 was added together with [Slurry 1] etc.

[0120] (evaluation) The above examples and comparative examples were evaluated as follows.

[0121] <Coloring degree> Using the fixing unit of a color multifunction printer (imagio MP C4500, manufactured by Ricoh Co., Ltd.), a 0.4 mg / cm2 ink was applied to plain paper. 2 A solid fixed image was formed and fixed at a fixing temperature of 130° C. The coloring degree of the image was measured at an average of five points using an X-Rite exact and evaluated according to the following evaluation criteria.

[0122] [Evaluation Criteria] ◎: Coloring level is 2 or higher ○: Coloring degree is 1.75 or more and less than 2 △: Coloring degree is 1.5 or more and less than 1.75 ×: Coloring degree is less than 1.5

[0123] <Fine line reproducibility> The toner obtained above was placed in a color multifunction printer (imagio MP C4500, manufactured by Ricoh Co., Ltd.) and a printing test of 6-point and 10-point characters was carried out. The reproducibility of the printed characters was evaluated according to the following evaluation criteria.

[0124] [Evaluation Criteria] ◎: 6-point characters are clear ○: Some of the 6-point characters are crushed. △: 10-point characters are clear ×: 10-point characters are partially blurred

[0125] The toners of the examples and comparative examples and their evaluation results are shown in Table 1. In the table, "Pes" stands for polyester resin, and "MEK" stands for methyl ethyl ketone.

[0126] [Table 1] [Prior art documents] [Patent documents]

[0127] [Patent Document 1] JP 2005-264120 A

Claims

1. a) kneading a colorant and a resin to prepare a master batch; b) preparing an oil phase by dissolving the masterbatch in an organic solvent; c) mixing an organic solvent and water to form an aqueous phase; d) adding the aqueous phase to the oil phase to effect phase inversion emulsification and obtain an oil-in-water dispersion, The method for producing a toner, wherein the step b comprises dissolving the master batch in the organic solvent and then neutralizing the master batch with an alkaline aqueous solution.

2. 2. The method for producing a toner according to claim 1, wherein the resin in step (a) is a polyester resin.

3. 3. The method for producing a toner according to claim 1, wherein in the step (b), the oil phase is prepared by using the master batch, the organic solvent, and a polyester resin.

4. 4. The method for producing a toner according to claim 1, wherein the organic solvent in the step b is the same as the organic solvent in the step c.

5. 5. The method for producing a toner according to claim 1, wherein the step c) comprises preparing an aqueous solution in which the organic solvent is dissolved in 80% or more of a saturated solubility amount of the organic solvent by using the organic solvent and the water.

6. 6. The method for producing a toner according to claim 1, wherein the organic solvent in the step b and the organic solvent in the step c are ethyl acetate.

7. 7. The method for producing a toner according to claim 1, further comprising the step of: e) aggregating the oil-in-water dispersion using an aggregating agent after the step d).

Citation Information

Patent Citations

  • Electrophotographic toner and method for producing the same

    JP2002296839A

  • Method for producing fine polymer particulate

    JP2005264120A

  • Toner, developer, image forming apparatus and process cartridge

    JP2007206431A

  • Toner having a core-shell structure and method for manufacturing the same

    JP2012517036A

  • Toner, toner manufacturing method, full-color image forming method, and process cartridge

    JP2013029757A